Ecological Modernization at the Intersection of Environment and Energy - Sezgin, Zeynep (International Journal of Energy Economics and Policy, 2013)
Contemporary environmental policy is marked by an emphasis on the fight against climate change. Technological improvements for energy efficiency and transition to a low carbon economy are seen as principal environmental policy measures. Has this been the case 40 years ago when modern environmental policy took its first leap? Or has it been the result of a particular twist in the course of the development of environmental policy? Taking sides with the latter approach, it is argued that the intertwining of environmental and energy policy is attributable to ecological modernization that has become the dominant interpretation of sustainable development. Accordingly, this article focuses on ecological modernization theory and policy strategy in an aim to capture this turn. Empirical evidence will be provided through an analysis of European Union (EU) environmental policy. It will be demonstrated how EU environmental policy takes its direction from ecological modernization and how energy efficiency lies at its core. Keywords: sustainable development; ecological modernization; fight against climate change JEL Classifications: Q01; Q54; Q56